Cattle Methane Emission and Pasture Carbon Dioxide Balance of a Grazed Grassland. Issue 3 (1st May 2014) - McGinn, S. M.; Beauchemin, K. A.; Coates, T.; McGeough, E. J.
Abstract : Grasslands constitute a major land use globally and are a potential sink of atmospheric carbon dioxide (CO2 ). They are also an important habitat for wildlife and a source of feed that supports ruminant livestock production. However, the presence of ruminants grazing these grasslands is also a source of methane (CH4 ) that contributes to buildup of greenhouse gases in the atmosphere. Our study measured enteric CH4 from 40 confined heifers in 1‐ha paddocks using a dispersion model and CO2 exchange from an adjacent grassland site using a micrometeorological technique. The study was conducted at a mixed prairie grassland located in southern Alberta, Canada. The mean (standard error) CH4 emission was 189 (± 6) g animal −1 d −1 over four campaigns (over a 3‐yr period). The daily averaged CO2 exchange from the grassland peaked at +2.2 g m −2 h −1 (sink) in early July and declined to negative values (source) in mid‐August. Annually, the grazed grassland was either a net sink for carbon (C) at +40 kg C ha −1 or a small source at −7 kg C ha −1 depending on a cattle stocking density of 0.1 or 0.2 animals ha −1, respectively. However, in basing the exchange on CO2 equivalence (CO2_eq ), both stocking densities resulted in the grazed grassland being a source of greenhouse gas of −9 or −338 kg CO2_eq ha −1 y −1 . This study illustrates the need to consider the cattle CH4 emissions and the stocking density when evaluating the environmental sustainability of grazed grasslands.